Ecology & field biology - Smith, Robert Leo; Smith, Robert Leo; Smith, Thomas M. (New York, Benjamin Cummings, 1966)
This book presents a comprehensive overview of all aspects of ecology, including evolution, ecosystems theory, practical applications, plants, animals, biogeochemical cycles, and global change. This balanced approach has made Ecology and Field Biology the best-selling ecology book on the market. New book purchase includes Evolution Lab from our BiologyLabs On-Line series, a subscription to The Biology Place Website, and access to the text-specific companion website.
Appendix A-C 722-771p.; Glossary G1-18p.; Bibliography B1-31p.; Acknowledgements A1-4p.; Index I1-19p.
Keywords: Ecological genetics; Ecosystem; Community